Sebaran Vegetasi Bunga Edelweis di Kawasan Taman Nasional Kelimutu dengan Citra Landsat 8 TM - Siki, Theodosia Monika; Pani, Emilianus; Semiun, Chatarina Gradict (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
Edelweis Anaphalis longifolia is one of Indonesia s mountain vegetation that grows at an altitude of 1 000 2 000 meters above sea level and plays a role as a pioneer plant in volcanic soils Anaphalis longifolia is one of the places in Kelimutu National Park which spans altitudes of 1 000 1 731 meters above sea level Using Landsat satellite imagery the research aims to identify environmental factors influencing edelweis distribution Data collection was conducted across six tracking routes: Moni Wologai Protelindo Dedumudi Niowula Ratebeke and Saga Bukit Sokoria combining field observations with the analysis of Landsat 8 imagery elevation SHP rock type SHP and NDVI values The results of the study show that the distribution of edelweis is most commonly found at an altitude of 1471 1599 meters above sea level Meanwhile the distribution of edelweis is at least at an altitude of 1114 1200 meters above sea level The types of rocks in the Kelimutu National Park area are young volcanic rocks and the distribution of edelweis tends to be more abundant in areas with moderate NDVI values 0 25 0 35 Environmental factors such as temperature humidity sunlight intensity soil pH and wind speed play a role in the spread of Edelweis in Kelimutu National Park < em>< p>